Energy saving potential of heat insulation solar glass: Key results from laboratory and in-situ testing. (15th February 2016) - Cuce, Erdem; Cuce, Pinar Mert; Young, Chin-Huai
Abstract: HISG (heat insulation solar glass) is a recently developed multi-functional glazing technology to mitigate energy consumption of buildings. HISG can generate electricity similar to conventional PV (photovoltaic) glazing products when exposed to sunlight, however it differs from them by having some extraordinary characteristic features such as thermal insulation, which is competitive with Argon filled triple glazed windows, acoustic comfort, remarkable energy saving potential and self-cleaning ability owing to TiO2 nano coating. Within the scope of this research, latest results from laboratory and in-situ testing of HISG are presented in terms of its key role in mitigating heating and cooling demand of buildings as well as clean energy generation. Lighting and thermal comfort related parameters such as shading coefficient, UV, IR and visible light intensity are also investigated through the tests conducted in real operating conditions. It is achieved from the results that instant electricity generation of HISG is 16% higher than that of standard PV glazing owing to its nano layer reflective film. Shading coefficient of HISG is only 0.136, which provides almost 80% reduction in solar heat gain compared to ordinary glazing. Indoor air temperature measured from HISG test house in summer time is very close to the ambient temperature, whereas it is found to be 14.7 °C higher in ordinary glass test house due to greenhouse effect. Annual heating and cooling demand tests indicate that HISG provides 38 and 48% energy saving in heating and cooling season, respectively. Highlights: Nano layer reflective film of HISG enables 16% more power generation. 80% of undesired outdoor thermal radiation is prevented by HISG. HISG has a 100% UV blocking rate. The shading coefficient of HISG is 0.136. HISG provides 38 and 48% energy saving in heating and cooling season.